2018
DOI: 10.18632/oncotarget.25479
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 induced cardiac hypertrophy via CREB/GSK3b/SOS1 pathway and metabolomics alterations

Abstract: The particle matter with diameter less 2.5μm (PM2.5) easier to adsorb toxic substance, and interfere with pulmonary gas exchange. In this study, cardioprotective effects of low molecular weight (LMW) fucoidan in cardiac hypertrophy subjects induced by PM2.5 exposure was conducted by measuring QT interval, Blood pressure, cardiac structure, metabolites and proteins expression in different organs. After PM2.5 exposure, increase in blood pressure, abnormal cardiac function (Prolongation of Action Potential Durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…After cessation of PM exposure, hyperlipidemia downregulated Fas gene expression and upregulated Hmgcs2 expression with negative feedback decreasing the hyperlipidemia to the normal level. These results indicated that PM 2.5 in poultry houses could cause hepatic dyslipidemia in broilers, which is also supported by published papers [ 26 , 29 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…After cessation of PM exposure, hyperlipidemia downregulated Fas gene expression and upregulated Hmgcs2 expression with negative feedback decreasing the hyperlipidemia to the normal level. These results indicated that PM 2.5 in poultry houses could cause hepatic dyslipidemia in broilers, which is also supported by published papers [ 26 , 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…Many studies have reported that PM 2.5 exposure can induce distinct inflammatory signaling in the lung and liver [ 24 ]. Tumor necrosis factor (TNF)-α associated hepatic dyslipidemia [ 25 ] and cardiac hypertrophy [ 26 ] cause liver fibrosis [ 27 , 28 ] and elevate the risk of oxidative stress-driven nonalcoholic fatty liver disease [ 29 ]. These cases suggested that PM 2.5 not only dwells in the lungs but also is likely to cross the air–blood barrier and adversely affect the liver through the blood circulation system.…”
Section: Introductionmentioning
confidence: 99%
“…Fine PM exposures can also lead to sustained detrimental effects in the heart by altering the transcription factor profile. One example of this has been shown previously in a cohort of PM 2.5 -exposed mice (89). Cardiac remodeling through hypertrophy, QT interval prolongation, and fibrosis were correlated with elevated cAMP response element-binding protein (CREB) as well as SOS Ras/Rac guanine nucleotide exchange factor 1 (SOS1) and glycogen synthase kinase-3␤ (GSK3␤) expression.…”
Section: H288mentioning
confidence: 61%
“…A wide array of studies using different experimental paradigms show pathological cardiac hypertrophy to be significantly attenuated by p38MAPK pathway inhibition [11,12,13]. p38MAPK pathway activity leads to the downstream activation of cyclic adenosine 3′,5′-monophosphate (cAMP)-response element binding protein (CREB), with CREB interacting with DNA and regulating a plethora of gene transcriptions strongly associated with LVH [14]. Brain-derived neurotrophic factor (BDNF) is also increased in LVH [15] and can contribute to LVH pathophysiology via two-way activation interactions with CREB, with increased BDNF also being induced by p38MAPK [16].…”
Section: Lvh Pathophysiologymentioning
confidence: 99%